PNPLA3 variant M148 causes resistance to starvation‐mediated lipid droplet autophagy in human hepatocytes. Issue 1 (1st September 2018) - Negoita, Florentina; Blomdahl, Julia; Wasserstrom, Sebastian; Winberg, Martin E.; Osmark, Peter; Larsson, Sara; Stenkula, Karin G.; Ekstedt, Mattias; Kechagias, Stergios; Holm, Cecilia; Jones, Helena A.
Abstract: The mechanism of how patatin‐like phospholipase domain‐containing protein 3 (PNPLA3) variant M148 is associated with increased risk of development of hepatic steatosis is still debated. Here, we propose a novel role of PNPLA3 as a key player during autophagosome formation in the process of lipophagy. A human hepatocyte cell line, HepG2 cells, expressing recombinant I148 or 148M, was used to study lipophagy under energy deprived conditions, and lipid droplet morphology was investigated using florescence microscopy, image analysis and biochemical assays. Autophagic flux was studied using the golden‐standard of LC3‐II turnover in combination with the well characterized GFP‐RFP‐LC3 vector. To discriminate between, perturbed autophagic initiation and lysosome functionality, lysosomes were characterized by Lysotracker staining and LAMP1 protein levels as well as activity and activation of cathepsin B. For validation, human liver biopsies genotyped for I148 and 148M were analyzed for the presence of LC3‐II and PNPLA3 on lipid droplets. We show that the M148‐PNPLA3 variant is associated with lipid droplets that are resistant to starvation‐mediated degradation. M148 expressing hepatocytes reveal decreased autophagic flux and reduced lipophagy. Both I148‐PNPLA3 and M148‐PNPLA3 colocalize and interact with LC3‐II, but the M148‐PNPLA3 variant has lower ability to bind LC3‐II. Together, our data indicate that PNPLA3 might play an essential role in lipophagy in hepatocytes and furthermore that the M148‐PNPLA3 variant appears to display a loss in this activity, leading to decreased lipophagy. Abstract : M148‐PNPLA3 overexpressing hepatocytes are characterized by lipid droplets resistant to degradation, decreased autophagic flux and lipophagy and impaired autophagosome formation. PNPLA3 colocalizes with LC3‐II on lipid droplets, interacts with LC3‐II, but is not degraded by the lysosome. Hepatocytes in Liver Samples from M148 Individuals Reveal Accumulation of LC3‐II  +  LDs with increased area and colocalized PNPLA3 and LC3 Puncta on LDs.